2014
DOI: 10.1155/2014/302903
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anthelmintic Treatment on Coccidia Oocyst Shedding in a Wild Mammal Host with Intermittent Cestode Infection

Abstract: While hosts are routinely exploited by a community of parasite species, the principles governing host responses towards parasites are unclear. Identifying the health outcomes of coinfections involving helminth macroparasites and microparasites is one area of importance for public and domestic animal health. For instance, it is controversial how deworming programmes affect incidence and severity of such important microparasite diseases as malaria. One problem is that most study systems involve domestic and labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Specifically, we found that the rates of ticks infected with bird-associated Borrelia spirochetes were lower if ticks fed on the hosts positive for avian haemosporidians. Therefore, this result is consistent with studies revealing that intracellular parasites, such as haemosporidians, can benefit from host immune systems prioritizing immune responses against extracellular parasites at the expense of immune responses against intracellular parasites [ 24 , 40 , 41 , 43 ]. The applicability of the hypothesis, based on the polarization of host immune responses, rests on the assumption that parasites eliciting conflicting immunological pathways are widespread in host populations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Specifically, we found that the rates of ticks infected with bird-associated Borrelia spirochetes were lower if ticks fed on the hosts positive for avian haemosporidians. Therefore, this result is consistent with studies revealing that intracellular parasites, such as haemosporidians, can benefit from host immune systems prioritizing immune responses against extracellular parasites at the expense of immune responses against intracellular parasites [ 24 , 40 , 41 , 43 ]. The applicability of the hypothesis, based on the polarization of host immune responses, rests on the assumption that parasites eliciting conflicting immunological pathways are widespread in host populations.…”
Section: Discussionsupporting
confidence: 90%
“…within hosts [ 24 , 35 , 36 ]. Analogously to the studies on extracellular bacterial parasites, multiple studies found a positive role of extracellular intestinal parasites in the prevalence and parasitaemia of different apicomplexans [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The undefined pattern in the prevalence of Eimeria infection among poultry with the different anthelminthic treatment regimens appears to be dicey in explanation. Although, a study conducted on a species of wild mammal (Alpinemarmot, M. marmota latirostris) by Václav and Blazeková (2014), reported that helminth infection has a protective effect on the reproductive rates of coccidia parasites as the use of anthelmintic decreases the shedding rate of Eimeria oocysts.…”
Section: Discussionmentioning
confidence: 99%